THE EFFECT OF PRODUCT QUALITY, PRICE AND PROMOTION ON ACER LAPTOP PURCHASE DECISIONSTO STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MALIKUSSALEH - Farhan Kandarifa; Samsul Bahri; Adnan; Rahmaniar (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of product quality, price, and promotion on the purchase decision of Acer laptops on students of the Faculty of Economics and Business, Universitas Malikussaleh. The sampling technique used is nonprobability sampling technique with purposive sampling method. This study used a sample of 96 respondents and analyzed then. Data collection using a Likert scale questionnaire. The data analysis method used is validity and reliability test, heteroscedasticity, multicollinearity, multiple linear regression, t-test, f-test, correlation coefficient, and determination coefficient with SPSS 20 application. The results of the study that have been conducted indicate that product quality and promotion have a significant effect partially and simultaneously on purchasing decisions. While price does not have a significant effect on purchasing decisions.